Validity and reliability of pencak silat achievement motivation instrument - Gandinni, Nanda Aprilia; Guntoro, Tri Setyo; Watiningsih, Rita; Nurhidayah, Dewi (Universitas Tanjungpura, 2025)
Background. Achievement motivation plays a crucial role in the performance of martial arts athletes and should be closely monitored and assessed by coaches. However, the absence of a specific instrument to measure achievement motivation in Setia Hati Terate athletes has made it difficult for coaches to evaluate their athletes